Tuning adhesion forces between functionalized gold colloidal nanoparticles and silicon AFM tips: role of ligands and capillary forces - Oras, Sven; Vlassov, Sergei; Berholts, Marta; Lõhmus, Rünno; Mougin, Karine (Beilstein Journal of Nanotechnology, 2018)
Adhesion forces between functionalized gold colloidal nanoparticles (Au NPs) and scanning probe microscope silicon tips were experimentally investigated by atomic force microscopy (AFM) equipped with PeakForce QNM (Quantitative Nanoscale Mechanics) module. Au NPs were synthesized by a seed-mediated process and then functionalized with thiols containing different functional groups: amino, hydroxy, methoxy, carboxy, methyl, and thiol. Adhesion measurements showed strong differences between NPs and silicon tip depending on the nature of the tail functional group. The dependence of the adhesion on ligand density for different thiols with identical functional tail-group was also demonstrated. The calculated contribution of the van der Waals (vdW) forces between particles was in good agreement with experimentally measured adhesive values. In addition, the adhesion forces were evaluated between flat Au films functionalized with the same molecular components and silicon tips to exclude the effect of particle shape on the adhesion values. Although adhesion values on flat substrates were higher than on their nanoparticle counterparts, the dependance on functional groups remained the same.
Keywords: adhesion; AFM; gold; nanoparticle functionalization; nanoparticles

Introduction to Tribology - Bhushan, B. (John Wiley & Sons, Ltd, 2013)

(untitled) - Bhushan, B.; Liu, H. (Phys. Rev. B, 2001)

(untitled) - Persson, B. N. J.; Scaraggi, M. (J. Chem. Phys., 2014)

(untitled) - Polyakov, B.; Vlassov, S.; Dorogin, L. M.; Kulis, P.; Kink, I.; Lõhmus, R. (Surf. Sci., 2012)

(untitled) - Casado, S. (Beilstein J. Nanotechnol., 2017)

Handbook of Nanotechnology - Bhushan, B. (Springer-Verlag, 2010)

(untitled) - Chang, J.-W.; Jung, M.; Kim, S. G.; Shim, S.-B.; Kim, J.; Lee, S. G.; Yoo, Y.; Kim, B. (J. Korean Phys. Soc., 2013)

Electromechanical Investigation of Low Dimensional Nanomaterials for NEMS Applications - Lu, H. (Rice University, 2011)

(untitled) - Kooij, E. S.; Ahmed, W.; Hellenthal, C.; Zandvliet, H. J. W.; Poelsema, B. (Colloids Surf., A, 2012)

(untitled) - Grzelczak, M.; Pérez-Juste, J.; Mulvaney, P.; Liz-Marzán, M. P. (Chem. Soc. Rev., 2008)

(untitled) - Fan, H. J.; Werner, P.; Zacharias, M. (Small, 2006)

(untitled) - Lee, G.-J.; Shin, S.-I.; Kim, Y.-C.; Oh, S.-G. (Mater. Chem. Phys., 2004)

(untitled) - Yin, P.-G.; You, T.-T.; Tan, E.-Z.; Li, J.; Lang, X.-F.; Jiang, L.; Guo, L. (J. Phys. Chem. C, 2011)

(untitled) - Chandrasekara, G.; Mougin, K.; Haidara, H.; Vidal, L.; Gnecco, E. (Appl. Surf. Sci., 2011)

(untitled) - Guo, D.; Xie, G.; Luo, J. (J. Phys. D: Appl. Phys., 2014)

(untitled) - Nikogeorgos, N.; Hunter, C. A.; Leggett, G. J. (Langmuir, 2012)

(untitled) - Polyakov, B.; Vlassov, S.; Dorogin, L. M.; Butikova, J.; Antsov, M.; Oras, S.; Lõhmus, R.; Kink, I. (Beilstein J. Nanotechnol., 2014)

(untitled) - Moazzez, B.; O’Brien, S. M.; Merschrod S, E. F. (Sensors, 2013)

(untitled) - Gnecco, E.; Nita, P.; Casado, S.; Pimentel, C.; Mougin, K.; Giordano, M. C.; Repetto, D.; Buatier de Mongeot, F. (Nanotechnology, 2014)

Fundamentals of Friction and Wear on the Nanoscale - Mougin, K.; Haidara, H. (Nanoscale Friction of Self-Assembled Monolayers, 2006)

(untitled) - Böhme, G.; Hohn, P.; Krupp, H.; Rabenhorst, H.; Schnabel, W.; Walter, G. (J. Appl. Phys., 1973)

(untitled) - Langbein, D. (J. Adhesion, 1969)

(untitled) - Darwich, S.; Mougin, K.; Rao, A.; Gnecco, E.; Jayaraman, S.; Haidara, H. (Beilstein J. Nanotechnol., 2011)

Nanoscale Materials in Chemistry - McKenna, K. P. (Unique Bonding in Nanoparticles and Powders, 2009)

(untitled) - Sperling, R. A.; Parak, W. J. (Philos. Trans. R. Soc., A, 2010)

(untitled) - Hofmeister, H. (Z. Kristallogr., 2009)

(untitled) - Mougin, K.; Haidara, H.; Castelein, G. (Colloids Surf., A, 2001)

(untitled) - Kessel, C. R.; Granick, S. (Langmuir, 1991)

(untitled) - Carson, A. G.; Granick, S. (J. Mater. Res., 1990)

(untitled) - Lio, A.; Charych, D. H.; Salmeron, M. (J. Phys. Chem. B, 1997)

(untitled) - McDermott, M. T.; Green, J.-B. D.; Porter, M. D. (Langmuir, 1997)

(untitled) - Asay, D. B.; Kim, S. H. (J. Phys. Chem. B, 2005)

Intermolecular and Surface Forces - Israelachvili, J. N. (Elsevier, 2011)

(untitled) - Ando, Y. (Wear, 2000)

(untitled) - Riedo, E.; Lévy, F.; Brune, H. (Phys. Rev. Lett., 2002)

(untitled) - Haidara, A.; Mougin, K.; Schultz, J. (Langmuir, 2000)

(untitled) - Noel, O.; Mazeren, P.-E.; Nasrallah, H. (Phys. Rev. Lett., 2012)

(untitled) - Harrsion, A. J.; Corti, D. S.; Beaudion, S. P. (Part. Sci. Technol., 2015)

Atomic Force Microscopy: Understanding Basic Modes and Advanced Applications - Haugstad, G. (Probing material properties II: Adhesive nanomechanics and mapping distance-dependent interactions, 2012)

(untitled) - Leite, F. L.; Bueno, C. C.; Da Roz, A. L.; Ziemath, E. C.; Oliviera, O. N., Jr (Int. J. Mol. Sci., 2012)

(untitled) - Komvopoulos, K. (Wear, 1996)

(untitled) - Bharathi, S.; Nogami, M.; Ikeda, S. (Langmuir, 2001)

(untitled) - Lin, S.-Y.; Tsai, Y.-T.; Chen, C.-C.; Lin, C.-M.; Chen, C.-h. (J. Phys. Chem. B, 2004)

(untitled) - Xiao, X.; Hu, J.; Charych, D. H.; Salmeron, M. (Langmuir, 1996)

Contact mechanics and Friction: Physical Principles and Applications - Popov, V. L. (Springer, 2010)

(untitled) - Frens, G. (Nature (London), Phys. Sci., 1973)

(untitled) - Grabar, K. C.; Allison, K. J.; Baker, B. E.; Bright, R. M.; Brown, K. R.; Freeman, R. G.; Fox, A. P.; Keating, C. D.; Musick, M. D.; Natan, M. J. (Langmuir, 1996)

(untitled) - Bastus, N. G.; Comenge, J.; Puntes, V. (Langmuir, 2011)

Colloidal Gold Nanoparticles: A study of their Drying-mediated Assembly in mesoscale aggregation patterns and of their AFM-assisted Nanomanipulation on model solid surfaces - Darwich, S. (University of Haute-Alsace, 2011)

(untitled) - Nuzzo, R. G.; Allara, D. L. (J. Am. Chem. Soc., 1983)

(untitled) - Mougin, K.; Gnecco, E.; Rao, A.; Cuberes, M. T.; Jayaraman, S.; McFarland, E. W.; Haidara, H.; Meyer, E. (Langmuir, 2008)

(untitled) - Lin, S.-Y.; Tsai, Y.-T.; Chen, C.-C.; Lin, C.-M.; Chen, C.-h. (J. Phys. Chem. B, 2004)